Through health workers' eyes: a qualitative study of health service provision for migrants at Schengen border - Mateja Žagar; Danica Rotar Pavlič; Igor Švab; Alem Maksuti; Boris Ilić; Martina Smrekar; Irena Kovačević (BMC, 2019)
Abstract Background Croatia and Slovenia were the transit countries on the Balkan route for migrants and refugees from Middle East countries in 2015 and 2016. They had to optimize health care delivery in the special circumstances in refugee camps and transit centres. Little is known about health care provision in border camps where a large number of migrants stay for only couple of hours. Previous studies emphasize that language barriers and cultural differences play a central part in the relationship between health workers and migrants inside the transit zone. The aim of the study was to identify specific characteristics of health care provision experienced by primary healthcare providers in order to prepare solutions on how to organise health care in refugee settings. Methods Twelve thematic interviews were conducted in the middle of the most intense migration movements to the North-West Europe between November and December 2015 with health workers from Croatia and Slovenia. Interview transcripts were read, coded, reviewed, and labelled. We used qualitative content analysis. Results Four themes about the health service provision for refugees at Schengen border were identified. The circumstance when mutual understanding is poor and the consultation not successful, cultural differences represent a central barrier. Participants highlighted that the importance of respecting human dignity is crucial for the provision of basic medical care for migrants in transit. Conclusion Successful overcoming language barriers, respecting cultural differences, humanity, susceptibility to social deprivation and traumatic experiences are the key factors important for organisation of health care in transit centers and camps. This article gives some useful tips for healthcare workers and policy makers who are participating in health services provision for migrants and other refugees. Health workers should be prepared to work in special working conditions with a lack of resources. Their work would require timely planning and reflection on the organization of more transit camps. Trial registration Ethical Committee of the Republic of Slovenia approved the study as a project number 112/02/16.